CsrA maximizes expression of the AcrAB multidrug resistance transporter. Issue 22 (13th October 2017) - Ricci, Vito; Attah, Victoria; Overton, Tim; Grainger, David C.; Piddock, Laura J.V.
Abstract: Carbon Storage Regulator A (CsrA) is an RNA binding protein that acts as a global regulator of diverse genes. Using a combination of genetics and biochemistry we show that CsrA binds directly to the 5′ end of the transcript encoding AcrAB. Deletion of csrA or mutagenesis of the CsrA binding sites reduced production of both AcrA and AcrB. Nucleotide substitutions at the 5′ UTR of acrA mRNA that could potentially weaken the inhibitory RNA secondary structure, allow for more efficient translation of the AcrAB proteins. Given the role of AcrAB-TolC in multi-drug efflux we suggest that CsrA is a potential drug target.